Migrants and disability following injury: findings from a prospective study in New Zealand. (9th July 2019) - Baker, Warinthon; Samaranayaka, Ari; Wyeth, Emma; Ameratunga, Shanthi; Derrett, Sarah
Abstract: Objectives : To compare the prevalence of disability between migrants and non‐migrants at three and 24 months post‐injury, and to identify key predictors of post‐injury disability among migrants. Methods : Disability among 2, 850 injured participants, including 677 migrants to New Zealand, was measured prospectively using the World Health Organization Disability Assessment Schedule. Results : Migrants experienced higher risk of disability than non‐migrants at three months post‐injury (aRR=1.14, 95%CI 1.03–1.26). Both groups had similar disability prevalence, but higher than pre‐injury, at 24 months. For migrants, strong predictors of disability at three months post‐injury were: higher injury severity, pre‐injury obesity, and perceiving the injury as a threat of disability. Having multiple chronic conditions was a predictor of disability at both time points. Conclusions : Disability was persistent for migrants and non‐migrants to 24 months post‐injury. The disability risk at three months was higher for migrants. Certain predictors associated with disability were identified. Implications for public health : Despite having accessed healthcare services for their injury, migrants (compared with non‐migrants) had higher risks of disability at least in the first three months post‐injury. Interventions should be focused during this critical period on identified key predictors to promote faster recovery and reduce disability.